Modulating the structure of plant-based protein dispersions - Ramadhan, Kurnia (2020)
The aim of the work presented in this thesis is to understand the formation of protein solidified gel network with controlled structures prepared from commercially established plant-based protein materials. Different types of soy protein isolates were characterised at various structural length scale. At molecular scale, results obtained from gel electrophoresis, scanning calorimetry, and infrared spectroscopy showed that variations in polypeptide constituents and protein conformations led to a different protein solubility in water. At mesoscopic length scale, soy protein isolates insoluble fraction was characterised as protein particles with diverse range of shapes and size distributions. At macroscale, viscoelastic behaviour of protein particles with the largest mean diameter size required the lowest isolate concentration due to their high dispersed phase volume.